Regard for the Other : Autothanatography in Rousseau, De Quincey, Baudelaire, and Wilde - Capucilli, Alyssa Satin, 1957- (Book collections on Project MUSE., 2017)
"Whether he's meeting the class pet, Nibbles, visiting the farm, or reading his favorite stories at the library, there is always loads of fun in store for Biscuit and his friends"--